Senam Lanjut Usia Terhadap Psikologi pada Orang Lanjut Usia di Kelurahan Heledulaa Selatan - Mulyadi, jesica -; Daud, Serly - (Universitas Negeri Gorontalo, 2025)
This community service activity aimed to improve the physical and psychological health of the elderly through elderly exercise (senam lansia) conducted in Heledulaa Selatan Village, Gorontalo City. Based on preliminary observations, most elderly people in the area rarely engage in regular physical activity, resulting in a high prevalence of degenerative diseases, insomnia, and anxiety. The activity was carried out on August 24, 2025, at Nabila Farma Pharmacy and involved 18 elderly participants. The implementation consisted of preparation, exercise sessions, health education, and evaluation through participant interviews. The results showed that after participating in the exercise, 83.33% of the elderly felt happier compared to before. Regular exercise helped reduce anxiety, improve mood, and enhance physical fitness. Physiologically, exercise stimulates the release of endorphins, which promote relaxation and feelings of happiness. Therefore, elderly exercise proved to have a positive impact on both physical and psychological health and is recommended to be conducted regularly and sustainably.Keywords: elderly exercise, anxiety, psychological health, elderly fitness, community service